Targeting autophagy to enhance chemotherapy and immunotherapy in oral cancer - Zeng, Xiaoli; Chen, Yue; Wang, Jing; He, Miao; Qiu, Junyao; Huang, Yun (Frontiers in Immunology, 2025)
Oral cancer is a highly malignant disease characterized by recurrence, metastasis, and poor prognosis. Autophagy, a catabolic process induced under stress conditions, has been shown to play a dual role in oral cancer development and therapy. Recent studies have identified that autophagy activation in oral epithelial cells suppresses cancer cell survival by inhibiting key pathways such as the mammalian target of rapamycin (mTOR) and mitogen-activated protein kinase (MAPK), while activating the adenosine monophosphate-activated protein kinase (AMPK) pathway. Inducing autophagy promotes degradation of eukaryotic initiation factor 4E, thus reducing metastasis and enhancing the efficacy of chemotherapy, radiotherapy, and immunotherapy. Furthermore, autophagy induction can modulate the tumor immune microenvironment and enhance antitumor immunity. This review comprehensively summarizes the relationship between autophagy and oral cancer, focusing on its mechanisms and therapeutic potential when combined with conventional treatments. While promising, the precise mechanisms and clinical applications of autophagy inducers in oral cancer therapy remain to be elucidated, offering new directions for future research to improve treatment outcomes and reduce recurrence.